Analysis of Soil Layer Characteristics on PT. Mining Roads Vale Indonesia Bahudopi Morowali Site Based on Cone Penetration Test (CPT) - Mahmud, Amir; Gusty, Sri; Chaerul, Muhammad (ASTONJADRO, 2025)
The location of this research was carried out in the mining concession area of PT. Vale site Bahudopi at 22 observation points. This research aims to analyze the characteristics of the soil and rock layers of the research area based on the Cone Penetration Test (CPT). The location of this research was carried out in the mining concession area of PT. Vale site Bahudopi at 22 observation points (Figure 1). The method used in this research is descriptive quantitative, namely, research that describes the conditions of a particular project with existing data, where the results obtained are data in the form of numbers. Meanwhile, data analysis uses quantitative descriptive analysis methods. The characteristics of the soil and rock layers of the research area based on the Cone Penetration Test (CPT) are: In the CPT data group in the northern part, it can be seen that the majority of rocks up to a depth of 4 meters have quite low friction sleeve and cone resistance values, namely below 20 kg/cm2. which indicates that the soil thickness is quite high in most parts of the area. In the CPT data group in the Southern part, it can be seen that the majority of rocks can be seen to have experienced several changes in hardness or pressure values, which can be seen from changes in qc and fs/FR values. From this, it can be concluded that the soil around the CPT data collection area is not homogeneous but still shows a tendency to be composed of the same type of rock but differs in friction sleeve and cone resistance values which could be caused by a high level of weathering so that the composition of the soil layers /soil is quite thick.